Rehabilitation criteria and indicators for the successful release of Javan hawk-eagle (Nisaetus bartelsi Stresemann, 1924) - AHMAD MUNAWIR; ANI MARDIASTUTI; BURHANUDDIN MASY’UD; DEWI MALIA PRAWIRADILAGA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Munawir A, Mardiastuti A, Masy’ud B, Prawiradilaga DM. 2024. Rehabilitation criteria and indicators for the successful release of Javan hawk-eagle (Nisaetus bartelsi Stresemann, 1924). Biodiversitas 25: 3491-3499. The Javan hawk-eagle (Nisaetus bartelsi Stresemann, 1924) is an endangered bird of prey that is native to Java Island and is protected by law. In order to save the species, rehabilitation programs are crucial for increasing its population in the wild. The current research aimed to establish criteria and indicators for rehabilitating Javan hawk-eagles and improving their chances of a successful release. Data were collected from literature review, interviews, and field observation. Collected data were scored based on a Likert scale and weighted on selected criteria and indicators, then described qualitatively. The research resulted in the identification of 34 criteria and 152 indicators. There were several rehabilitation stages observed in this research: 1) acceptance stage with 10 criteria and 30 indicators; 2) isolation stage with as many as six criteria and 18 indicators; 3) treatment stage with as many as four criteria and 12 indicators; 4) pre-training stage with as many as five criteria and 15 indicators, 5) training stage with five criteria and 65 indicators, and 6) habituation stage with four criteria and 15 indicators. The testing of 12 Javan hawk-eagle individuals at the Javan Hawk-eagle Sanctuary Center (JHESC), along with the developed criteria and indicators, could be feasible for rehabilitation standards to release Javan hawk-eagles successfully. According to the decision tree, nine out of the 12 individuals went through four stages, one went through three stages, and two went through two stages. In summary, the criteria and indicators have increased potential numbers and accelerated the rehabilitation process for the success of Javan hawk-eagle release.